On Some Types of Matrices for Fan Plane Graph and Their Dual - Haneen Mohammed Adil; Israa Munir Tawfik (Tikrit Journal of Pure Science, 2023)
This work aims to discuss the adjacency matrices, Incidence matrix and Degree matrix of some types plane graphs we usually used them, as complete graphs, cycle graph,…,ect. To find the dual of graph and transformation of the graph and their dual for some theorems to prove general cases.